A rare case of traumatic intramural hematoma in pediatric age group successfully managed with expectant approach - Kurian, Elizabeth; Joseph, Jijo; Thomas, Geido Davis; Anand, Rajeev (International Journal of Advances in Medicine, 2022)
Acute colonic intramural hematoma is a rare clinical entity. In most cases reported in literature a surgical management is used. Here we present a case of an 8-year-old boy who was found to have a colonic intramural hematoma following a fall from bicycle. Considering the age of the child and hemodynamic stability a conservative management was adopted and the child was successfully managed.